Pengaruh Media Pembelajaran Animasi Komputer Terhadap Hasil Belajar Ekonomi Siswa Kelas XI SMAN 1 Keruak: The Influence of Computer Animation Learning Media on Economics Learning Outcomes of Class XI Students at SMAN 1 Keruak - M. Saipul Watoni (Al-Gafari : Manajemen dan Pendidikan, 2025)
Teachers are required to be able to understand, master, and be able to use the available tools in an effort to achieve the expected teaching objectives. For that, teachers must have sufficient knowledge and understanding of learning media. This study aims to determine the effect of computer animation learning media on the learning outcomes of class XI students of SMAN 1 Keruak. This study was conducted at SMAN 1 Keruak. The research method used was a quasi-experimental study, involving 58 students of class XI IPS2 and XI IPS3 which were determined by cluster random sampling technique. Class XI IPS2 as the experimental class and XI IPS3 as the control class. The design of this study was a "nonequvalent control group design". The instrument in this study was a learning outcome test. Data were analyzed by t-test. Based on the results of data analysis, the learning outcomes of students in the experimental group were higher (mean 73.84, median 77.49, mode 90.5) than the control group (mean 67.57, median 71.5, mode 73.17) and from the results of the "t" test calculation, the tcount value was 2.15 while the ttable was 2.033 at a significant level of 0.05 or tcount>ttable or (2.15>2.033). So it can be concluded to reject Ho and accept Ha which states that there is a positive and significant influence of the use of computer animation learning media on the economic learning outcomes of class XI students of SMAN 1 Keruak. This shows that learning with computer animation learning media has a positive or significant influence on students' economic learning outcomes.